El seguimiento de la implementación de los Acuerdos de La Habana por las Organizaciones regionales: la OEA y la OEI - Presta Novello, Déborah (Cultura giuridica e diritto vivente, 2020)
[The monitoring of the implementation of the Havana Agreements by regional organizations: the OAS and the OEI] At the end of 2016, the Government of Colombia and the FARC-EP managed to sign a Peace Agreement to end the longest armed conflict in Latin America, known as the Havana Agreements. However, the implementation phase of the Agreements is extremely fragile and the institutionalized international community plays a key role in the success of this procedure. The Peace Agreement assigned the regional organizations very specific functions in terms of monitoring the implementation of each of the six points agreed upon. This investigation analyzes the results obtained through the monitoring and accompaniment work of the Organization of American States –OAS- and the Organization of Ibero-American States for Education, Science and Culture –OEI- reflected in the official reports published in this regard.